Tonsils at Telethon: developing a standardised collection of tonsil photographs for group A streptococcal (GAS) research - Mullane, Marianne J.; Thomas, Hannah M.; Carapetis, Jonathan R.; Lizama, Catalina; Billingham, Wesley; Cooper, Matthew N.; Everest, Christine; Sampson, Claudia R.; Newall, Nelly; Pearce, Sarah; Lannigan, Francis; McNulty, Eamonn; et al. (Frontiers in Pediatrics, 2024)
Introduction. Group A streptococcus (GAS) infections, such as pharyngitis and impetigo, can lead to rheumatic fever and rheumatic heart disease (RHD). Australian Aboriginal and Torres Strait Islander populations experience high rates of RHD and GAS skin infection, yet rates of GAS pharyngitis are unclear. Anecdotally, clinical presentations of pharyngitis, including tonsillar hypertrophy and sore throat, are uncommon. This study aimed to develop a standardised set of tonsil photographs and determine tonsil size distribution from an urban paediatric population.A prospective cohort of children aged 3 -15 years were recruited at the public events 'Discover Day' and 'Telethon Weekend' (October 2017) in Perth, Western Australia, Australia. Tonsil photographs, symptomatology, and GAS rapid antigen detection tests (RADT) were collected. Tonsil size was graded from the photographs using the Brodsky Grading Scale of tonsillar hypertrophy (Brodsky) by two independent clinicians, and inter-rater reliability calculated. Pharyngitis symptoms and GAS RADT were correlated, and immediate results provided.Results. Four hundred and twenty-six healthy children participated in the study over three days. The median age was seven years (interquartile range [IQR] 5.9-9.7 years). Tonsil photographs were collected for 92% of participants, of which 62% were rated as good-quality photographs and 79% were deemed of adequate quality for assessment by both clinicians. When scored by two independent clinicians, 57% received the same grade. Average Brodsky grades (between clinicians) were 11%, 35%, 28%, 22% and 5% of grades 0,1,2,3 and 4, respectively. There was moderate agreement in grading using photographs, and minimal to weak agreement for signs of infection. Of 394 participants, 8% reported a sore throat. Of 334 GAS RADT performed, <1% were positive.Discussion. We report the first standardised use of paediatric tonsil photographs to assess tonsil size in urban-living Australian children. This provides a proof of concept from an urban-living cohort that